Preferences for Advance Directives in Korea - So-Sun Kim; Won-Hee Lee; JooYoung Cheon; Jung-Eun Lee; KiSun Yeo; JuHee Lee (Nursing Research and Practice)
Background. The goal of advance directives is to help patients retain their dignity and autonomy by making their own decisions regarding end-stage medical treatment. The purpose of this study was to examine preferences of advance directives among general population in Korea. Method. A descriptive cross-sectional survey was performed from October 2007 to June 2008 in Seoul, Korea. A total of 336 city-dwelling adults self-administered the questionnaire and returned it via mail. Data analyses were conducted using SPSS 17.0. Results. Subjects reported the need for healthcare providers' detailed explanations and recommendations regarding end-of-life care. When there is no hope of recovery and death is imminent, most subjects did not want to receive cardiopulmonary resuscitation nor an IV or tube feeding. However, most of the subjects wanted pain management care. Conclusions. The present study showed that many Korean people have an interest in advance directives. The results show that the autonomy and dignity of patient have increased in importance. To provide better end-of-life care, there is a need to educate patients on the definition and intent of an advance directive. Additional proactive communication between patients and their caregivers should be educated to healthcare providers.